STRATEGIC MANAGEMENT IN TEACHER COMPETENCY DEVELOPMENT: A CASE STUDY - Imam Junaris (Nurul Jadid University, Probolinggo, East Java, Indonesia, 2021)
The study aims to analyze the implementation of strategic management for teacher competency development in SMA Darul Ulum 2 Unggulan BPPT CIS ID 113 Jombang. This research utilizes a qualitative approach with a type of case study. Data collection techniques use in-depth interviews, participant observation, and documentation. The collected data are investigated by presenting, reducing, and drawing conclusions. The results show that the strategic implementation of teacher competence consists of three program development activities, budget development, and procedure development. Program development is prioritized to enhance teacher competence through workshops, training education, further study education, MGMP/Teachers Professional Development Forum, KKG/Teacher Working Group, inclusive activities, training, in-service training, formation of teaching support, face to face training, online training, comparative studies, charity action, regular vacation, as well as compensation and visits to orphans, the poor and nursing homes.